2017
DOI: 10.1038/ncomms14414
|View full text |Cite
|
Sign up to set email alerts
|

Sansanmycin natural product analogues as potent and selective anti-mycobacterials that inhibit lipid I biosynthesis

Abstract: Tuberculosis (TB) is responsible for enormous global morbidity and mortality, and current treatment regimens rely on the use of drugs that have been in use for more than 40 years. Owing to widespread resistance to these therapies, new drugs are desperately needed to control the TB disease burden. Herein, we describe the rapid synthesis of analogues of the sansanmycin uridylpeptide natural products that represent promising new TB drug leads. The compounds exhibit potent and selective inhibition of Mycobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…However, targeting these vital cellular components may cause serious non‐specific effects to the host. On the other hand, the intricate network of metabolic pathways provide novel avenues for specific targeting of pathogens (Boshoff et al , ; Tran et al , ). Among these, arginine biosynthesis pathway is essential for the survival and pathogenesis of Mtb .…”
Section: Introductionmentioning
confidence: 99%
“…However, targeting these vital cellular components may cause serious non‐specific effects to the host. On the other hand, the intricate network of metabolic pathways provide novel avenues for specific targeting of pathogens (Boshoff et al , ; Tran et al , ). Among these, arginine biosynthesis pathway is essential for the survival and pathogenesis of Mtb .…”
Section: Introductionmentioning
confidence: 99%
“…Selected microbial peptides are known to exhibit antimycobacterial properties, spanning a range of distinctive molecular targets. For example, bacterial lassomycin from Lentzea kentuckyensis targets an essential mycobacterial ATP-dependent protease (ClpC1P1P2) (17), sansanmycin from a Streptomyces species inhibits phosphor-MurNAcpentapeptide translocase involved in the synthesis of mycobacterial lipid I (18), and capreomycin from Streptomyces capreolus inhibits L12-L10 to disrupt ribosomal GTPase activity and ribosome-dependent protein synthesis (19,20). Similarly, fungal calpinactam from Mortierella alpine affects mycobacterial cell wall biosynthesis (21,22), while trichoderins from a marine sponge-derived Tricoderma species obstruct mycobacterial ATP synthesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Three aspartic acid residues in E. coli MraY (Asp-115, Asp-116, Asp-267), found on cytoplasmic loops, were shown to be essential for activity, and it has been proposed that two Asp residues bind the active site Mg 2+ cofactor, while the third may be a catalytic nucleophile [69]. The possibility that the mureidomycins might be mechanism-based inhibitors, reacting via the enamide functional group, which might be expected to be chemically reactive, has been found not to be the case, from studies on model enamide-containing analogues [72], and since synthetic dihydropacidamycin and dihydrosansanmycin analogues retain MraY inhibition [20,21,24]. The observed slow-binding inhibition is therefore probably due to a conformational change in the protein structure, discussed in Section 2.2.…”
Section: The Muraymycin Group Of Lipo-ureidylpeptide Nucleoside Antibmentioning
confidence: 99%
“…They have reported that meta-tyrosine in the amino-terminal position is considerably more active than L-Tyr, and that the stereochemistry of the 2,3-diaminobutyric acid is important for both MraY inhibition and antimicrobial activity [23]. The anti-TB activity of the sansanmycin series has been developed signifcantly by Payne and co-workers, via chemical synthesis of a set of dihydrosansanmycin analogues [24]. They found that dihydrosansamycin B had significantly improved anti-TB activity (MIC50 0.3 µM) compared with sansanmycin B (MIC50 9.5 µM).…”
mentioning
confidence: 99%
See 1 more Smart Citation